PROBLEMS OF THE INTERNAL SYSTEM OF UZBEK WORDS - F.Shodiev (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
Analysis and generalization the investigation on studying one-rooted words in Turkish, studying the phonetically structure of onerooted words on originality / unoridinality, as their place and importance in modern Uzbek lexic.